Խորհրդապատկերների կերտման որոշ առանձնահատկություններ Գրիգոր Նարեկացու տաղերում - Թամրազյան, Արուսյակ (Մատենադարան)
The article analyzes the ode to the Mother of God by Grigor Narekats‘i (titled "Ode for the Church", "Ode for the Nativity", "Praise to the Church of St. Shoghakat‘"), underscoring its linguistic-symbolic structure. The structural integrity of the ode is considered in a variety of ways: its language (recurring words, doublets, embellishing and florid words, imaginative reflections, ambiguous words and expressions that are mostly untranslatable), synthesis of symbols used as ornaments in the portrayal of Mary, their sequence in this symbolic “syntax” (expression that among medieval Armenian authors seems to be limited to works by Grigor Narekats‘i), poetic devices, and symbolic composition. The latter is expressed a) through musical imagery – symbol of integrating two worlds, b) in the descent-ascent motif, c) in the gradual emergence of the image of Mary and her eventual departure, d) in a detailed description of the image of Mary-the Church in parallel with the Descending Light [Shoghakat‘]. In this context, the vocabulary of the ode is examined with some new interpretations of certain symbols and their biblical sources. The article also discusses the liturgical basis of the composition, its various adaptations in the Armenian hymnographic tradition, their neumatic notation and, due to the richness of their symbolic layers, the different configurations of certain odes by Narekats‘i in various manuscripts, in liturgical canons for various feast-days. В статье представлена ода Богородице (варианты названия – “Ода Церкви”, “Ода Рождества”, “Хвала Церкви Святого Шохаката”119) Григора Нарекаци в целостности ее словестно-символической ткани. Этой целостности служат все средства: язык (амбивалентные слова и выражения, слова-орнаменты, слова-дублеты; языковые-образные разветвления, в большинстве своем непереводимые), синтез, слияние или трансформация символов, обрамляющих образ Марии, их череда в этом символическом “синтаксисе” (выражение, которое из средневековых армянских авторов применимо, наверное, только к Григору Нарекаци), поэтические средства и символическая композиция. Последняя выражается а) в образе музыки, как символа взимопроникновения и полного единения двух миров б) в движении нисхождения-восхождения, в) в движении приближения – конкретизации образа – удалении, г) в детальном описании образа Марии-церкви параллельно с нисхождением света [Шохакат]. Более детально в этом контексте обсуждаются словарь оды, предлагаются новые варианты толкований, уточняются библейские источники некоторых символов. Также представлена ритуальная основа композиции, ее разнообразное использование в армянской гимнографической традиции, невменная нотация, и, в связи с наличием богатства символических слоев, разные сочетания од Нарекаци в разных канонах – церковных праздниках.
Keywords: Բառահյուսվածք